Belgian labour in World War II : strategies of survival, organisations and labour relations - Luyten, Dirk; Hemmerijckx, Rik (2000)
"Dirk Luyten; Rik Hemmerijckx Overdruk uit European Review of History, vol. 7, nr. 2, 2000"